INFLUENCE OF PROLONGED CENTRAL DEPRIVATION OF TESTOSTERONE SYNTHESIS ON PRODUCTION OF REACTIVE OXYGEN AND NITROGEN SPECIES AND MORPHOLOGICAL STRUCTURE OF RAT TESTES - Stetsuk, Ye.V.; Akimov, O.Ye.; Shepitko, V.I.; Goltsev, A.N. (World of Medicine and Biology, 2020)
Some testicular diseases require long-term use of testosterone synthesis blockers. It is known that testosterone is a necessary component for the physiological cooperation of cell forms of the stroma and parenchyma of testes. The scientific literature contains a limited amount of data about the effect of long-term deprivation of testosterone synthesis on this cooperation. The aim of our study was to establish the effect of long-term (365 days) inhibition of hypothalamic-pituitary stimulation of spermatogenesis on morphological and biochemical parameters in rat testes. Central deprivation of testosterone synthesis leads to fibrosis with subsequent disruption of the structural organization of the convoluted seminiferous tubules, hemodynamic disorders, endothelial dysfunction, increased density of blood vessel walls and systemic congestion. A decrease in the activity of constitutive NO synthase isoforms plays a major role in the development of structural changes in the testes of rats.